2013
DOI: 10.1371/journal.pone.0080653
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Unique and Generalist Microbes in Distantly Related Sympatric Intertidal Marine Sponges (Porifera: Demospongiae)

Abstract: The diversity and specificity of microbial communities in marine environments is a key aspect of the ecology and evolution of both the eukaryotic hosts and their associated prokaryotes. Marine sponges harbor phylogenetically diverse and complex microbial lineages. Here, we investigated the sponge bacterial community and distribution patterns of microbes in three sympatric intertidal marine demosponges, Hymeniacidon perlevis, Ophlitaspongia papilla and Polymastia penicillus, from the Atlantic coast of Portugal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 69 publications
0
26
0
2
Order By: Relevance
“…To our knowledge, this is the first report of Acidobacteria reaching abundances up to 79% in a sponge microbiome, where the dominant phyla that have been reported are either Proteobacteria (e.g. [ 9 , 14 ]) or Chloroflexi [ 2 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first report of Acidobacteria reaching abundances up to 79% in a sponge microbiome, where the dominant phyla that have been reported are either Proteobacteria (e.g. [ 9 , 14 ]) or Chloroflexi [ 2 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The diversity and specificity of microbial communities in marine organisms is a key aspect of the ecology and evolutionary relationships between both the eukaryotic hosts and their associated prokaryotes. To date, 32 major bacterial phyla and several possibly novel sponge-associated bacterial communities have been identified [ 9 ]. Nevertheless, most studies have focused on sponges of high latitudes and very little is known about the structure of microbial communities associated with sponges of tropical seas.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the analysis supported the presence of monophyletic, sponge-specific 16S rRNA sequence clusters. More recently, new scientific contributes allowed for describing the presence of about 40 phyla or candidate phyla, with the predominance of Proteobacteria, Actinobacteria, Chloroflexi, Bacteroidetes, and Cyanobacteria [34][35][36][37], and confirm the existence of sponge-specific clusters, among which the candidate phylum Poribacteria [33] and Candidatus Synechococcus spongiarum [38].…”
Section: Poriferamentioning
confidence: 99%
“…Other major themes addressed are the specificity or the ubiquity of the sponge microbiome (Erwin et al 2012a, Alex et al 2013, Webster et al 2013b) and the sponge symbiotic metabolism (Hunting et al 2010, Thomas et al 2010a, Freeman et al 2013. Additionally, there are number of papers on spatiotemporal dynamics of associated microbial communities assessing bacterial and also archaeal biodiversity (Sacristán-Soriano et al 2011b, Bjork et al 2013, Hardoim and Costa 2014.…”
Section: Sponge Chemical Ecology and Microbial Ecologymentioning
confidence: 99%
“…In fact, several dozen papers have already assessed the specificity of these sponge-associated communities (e.g. Erwin et al 2012a, Alex et al 2013, Webster et al 2013b, while others have shown that some symbiotic microorganisms can play a role as producers of biologically active compounds (Penesyan et al 2009, Genta-Jouve and Thomas 2012, Indaningrat et al 2016). In addition, there is another aspect that must be taken into account when assessing symbiont diversity and variability: different methods might influence the microbial community recovered, as shown by .…”
Section: Sponge Chemical and Microbial Ecology: Past Present And Futurementioning
confidence: 99%